Effect of berberine on cognitive function and β-amyloid precursor protein in Alzheimer’s disease models: a systematic review and meta-analysis - Liu, Jia-Yang; Dai, Yu; He, Yao-Xi; Lin, Lin (Frontiers in Pharmacology, 2024)
Berberine is an isoquinoline alkaloid extracted from Berberis vulgaris, which possesses a variety of pharmacological activities. Alzheimer's disease (AD) is a complex disease with multiple pathologic factors, with cognitive decline being the main manifestation of AD. The neuroprotective effects of berberine in animal models of Alzheimer's disease (AD) have been widely reported, exhibiting protective effects against risk factors associated with AD. In this study, we summarize and evaluate the effects of berberine on cognitive function and β-amyloid precursor protein in animal models of AD.: Eligible studies were retrieved from PubMed, MEDLINE, EMBASE, Web of Science, and Cochrane Library databases up to June 1, 2023. Risk of bias was assessed by the Systematic Review Center for Laboratory Animal Experiments (SYRCLE). Statistical analyses were performed using STATA 14.0 and Review Manger 5.4 software to calculate weighted standardized mean deviation (SMD) and 95% confidence intervals (CI), Morris water maze (MWM) test and β-amyloid precursor protein as outcome measures. Heterogeneity was tested using the I² test.Sensitivity analysis and publication bias were also assessed.Results: 19 studies involving 360 animals met the inclusion criteria, and the results of the meta-analysis showed that berberine decreased escape latency (SMD = -2.19, 95% CI: (-2.50, -1.88), P < 0.00001), increased the number of platform crossings (SMD = 4.27, 95% CI (3.38, 5.17), P < 0.00001), time in the target quadrant (SMD = 5.92, 95% CI (4.43, 7.41), P < 0.00001) and APP expression (SMD = 0.73, 95% CI: (0.25, 1.21), P = 0.003).Berberine can regulate APP expression and improve cognitive function in animal models of AD, and the mechanism may be related to the involvement of berberine in APP processing and influence the expression of its related factors.